Copper deposition in Wilson’s disease causes male fertility decline by impairing reproductive hormone release through inducing apoptosis and inhibiting ERK signal in hypothalamic-pituitary of mice - Wang, Tingting; Wu, Limin; Chen, Qiuying; Chen, Kuiyu; Tan, Fang; Liu, Jiabo; Liu, Xiang; Han, Hui (Frontiers in Endocrinology, 2022)
Wilson disease (WD) is an autosomal recessive disorder of copper metabolism characterized by liver and central nervous system dysfunction. Considerable evidence suggests that infertility are also very common in male patients with WD, but the exact molecular mechanisms involved remain unknown. In order to further study the pathological changes and its mechanisms in hypothalamic-pituitary-testicular (HPT) axis. Mice were divided into normal control group (NC), Wilson disease model TX mice group (WD), dimercaptosuccinic acid treated TX mice group (DMSA) and pregnant horse serum gonadotropin treated TX mice group（PMSG）. The copper content and morphology of hypothalamus and pituitary tissues, ultrastructure and apoptosis of hypothalamus neurons and pituitary gonadotropin cells, serum levels of reproductive hormone，pregnancy rate and litter size of the female mice were studied. The expression of apoptosis-related proteins and the phosphorylation of extracellular regulatory protein kinase (ERK1/2) in hypothalamus and pituitary were detected. The results showed that copper content was significantly increased in WD group, and histopathological morphology and ultrastructure of hypothalamus and pituitary were damaged. The levels of gonadotropin-releasing hormone (GnRH), follicle-stimulating hormone (FSH), luteinizing hormone (LH) and testosterone (T) were significantly decreased. The apoptosis rate in hypothalamus and pituitary was significantly increased. The expressions of pro-apoptotic proteins Bax and Caspase-3 were significantly increased, the expression of anti-apoptotic protein Bcl-2 was significantly decreased, and the phosphorylation level of ERK1/2 was significantly decreased. Fertility is significantly reduced. After DMSA intervention, the hypothalamus tissue copper content decreased, the hypothalamus and pituitary tissue morphology and ultrastructure were improved, cell apoptosis was alleviated, the expression of Bax and Caspase-3 was significantly increased, the expression of Bcl-2 was significantly decreased, and the reproductive hormone level, phosphorylation level and fertility were increased. Fertility were rescued after treatment with PMSG in male TX mice. These results suggest that copper deposition in Wilson's disease causes male fertility decline by impairing reproductive neuroendocrine hormone release through inducing apoptosis and inhibiting ERK signal in hypothalamic-pituitary. This study can also provide reference for the damage of copper pollution to male reproductive system.